The 1998 floods and beyond: towards comprehensive food security in Bangladesh - Dorosh, Paul A.; del Ninno, Carlo; Shahabuddin, Quazi (University Press Limited, 2004)
This book is a comprehensive analysis of the impact of the 1998 floods, the response of the government, and the coping strategies of households. It contains valuable lessons for developing countries on maintaining food security following major production shortfalls and serves as a guide for future research and decisionmaking on ways to address chronic food insecurity in Bangladesh.